2002
DOI: 10.1074/jbc.m112216200
|View full text |Cite
|
Sign up to set email alerts
|

5-Hydroxytryptamine 4(a) Receptor Is Coupled to the Gα Subunit of Heterotrimeric G13 Protein

Abstract: Serotonin (5-hydroxytryptamine (5-HT)) is an important neurotransmitter that regulates multiple events in the central nervous system. Many of the 5-HT functions are mediated via G protein-coupled receptors that are coupled to multiple heterotrimeric G proteins, including G(s), G(i), and G(q) subfamilies (Martin, G. R., Eglen, R. M., Hamblin, M. W., Hoyer, D., and Yocca, F. (1998) Trends Pharmacol. Sci. 19, 2-4). Here we show for the first time that the 5-hydroxytryptamine 4(a) receptor (5-HT(4(a))) is coupled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
127
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(132 citation statements)
references
References 50 publications
5
127
0
Order By: Relevance
“…This suggests that a G-protein other than G␣ q might be responsible for at least the majority of the observed constitutive activation of SRE. G 12/13 has previously been suggested to mediate the coupling of several other 7TM receptors to SRE activation through Rho kinase (32). The specific Rho kinase blocker Y-27632 decreased the basal SRE activity in GPR39-transfected cells by ϳ50%, indicating that G 12/13 is involved in the GPR39-induced, ligand-independent stimulation of SRE activation.…”
Section: Figmentioning
confidence: 94%
See 1 more Smart Citation
“…This suggests that a G-protein other than G␣ q might be responsible for at least the majority of the observed constitutive activation of SRE. G 12/13 has previously been suggested to mediate the coupling of several other 7TM receptors to SRE activation through Rho kinase (32). The specific Rho kinase blocker Y-27632 decreased the basal SRE activity in GPR39-transfected cells by ϳ50%, indicating that G 12/13 is involved in the GPR39-induced, ligand-independent stimulation of SRE activation.…”
Section: Figmentioning
confidence: 94%
“…Signaling through the SRE Pathway-Transcriptional regulation through the SRE pathway has been proposed to be stimulated by various G protein systems, including G␣ 13 , G␣ I , and G␤␥ (32)(33)(34)(35).…”
Section: Resultsmentioning
confidence: 99%
“…We recently demonstrated coupling between the 5-HT 4 receptor and G13-protein (Ponimaskin et al, 2002). We also have shown that 5-HT 4 receptor-dependent activation of G␣13 leads to RhoA-mediated cell rounding and neurite retraction.…”
Section: Introductionmentioning
confidence: 96%
“…Construction of the 5-HT 4 -pTracer-CMV2 plasmid has been described previously (Ponimaskin et al, 2002). To create 5-HT 7 -green fluorescent protein (GFP) and 5-HT 4 -GFP chimeras with C-terminal GFP fusion, receptor-coding sequences were amplified by PCR and then ligated into the pEGFP-N1 plasmid (Clontech, Cambridge, UK).…”
Section: Methodsmentioning
confidence: 99%
“…5-HT 4 Rs are coupled to the G s /cAMP/protein kinase A pathway (9). Other signal transduction pathways have also been reported, but mainly in heterologous transfected cells (2,10,11).…”
Section: -Hydroxytryptamine 4 Receptors (5-htmentioning
confidence: 99%